Analisis Potensi Mahasiswa untuk Mengembangkan Peran Sebagai Amil Zakat - Habaib, Nur Muhammad; Fadhilah, Rosyida Nur; Renfiana, Lilis (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2023)
This study aims to determine the capacity of Esy IAIN Metro students class of 2021 in improving their role as amil zakat. The background of this research is based on the need to know the level of understanding and readiness of students in fulfilling their responsibilities as amil zakat. This research utilizes qualitative methodology, specifically by using the case study method. This research was conducted by conducting in-depth interviews, participatory observation, and analyzing the information collected. The results showed that students have a good understanding of the meaning of amil zakat, although they still need improvement in their knowledge and practical implementation. Strategies are needed to foster practical skills and awareness in the higher education environment using a comprehensive approach. It is hoped that this research will be useful to build a foundation for the creation of programs that assist Esy IAIN Metro students in fulfilling their responsibilities as amil zakat